2022
DOI: 10.1155/2022/9074294
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Hepatitis B Vaccination Status and Associated Factors among Healthcare Workers in Bosaso, Puntland, Somalia 2020

Abstract: Introduction. Hepatitis B virus disease is a viral infection caused by the hepatitis B virus (HBV), which is a major public health problem worldwide. According to the World Health Organization (WHO) estimate, two billion people worldwide have serologic evidence of past or present HBV infection. The risk of infection is high among health professionals due to the risk of occupational contact with fluids of infected patients and the risk of needle stick injury. This study is aimed at assessing HBV vaccination cov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 27 publications
3
7
1
Order By: Relevance
“…Therefore, it is important that the ministry of health consider HBV vaccine supply throughout lower and higher levels of facilities in order to increase uptake in these disadvantaged facilities. However, the findings are quite similar to the study conducted in Somalia where only 56% of HCWs had received HBV vaccine with very low completion rate of 16.6% (17). This shows that HCWs need to be sensitized more on vaccine completion because most of them showed higher noncompletion status.…”
Section: Discussionsupporting
confidence: 81%
“…Therefore, it is important that the ministry of health consider HBV vaccine supply throughout lower and higher levels of facilities in order to increase uptake in these disadvantaged facilities. However, the findings are quite similar to the study conducted in Somalia where only 56% of HCWs had received HBV vaccine with very low completion rate of 16.6% (17). This shows that HCWs need to be sensitized more on vaccine completion because most of them showed higher noncompletion status.…”
Section: Discussionsupporting
confidence: 81%
“…Still, finding from this current study is higher than what was observed by other studies in Africa. For instance, complete vaccination coverage (≥ 3 doses) was reported by Biset AM & Adugna HB, 2017 to be 28.7% in Ethiopia [33], 24.5% in Cameroon by Noubiap et al ., 2014 [34], 16.4% in Somalia by Hussein et al [35], 12.9% in Ethiopia by Abebaw et al [36] and 10.9% in Burkina Faso by Ouédraogo et al [37]. This brings to the fore, the generally low vaccination coverage in Ghana and African at large [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Adugna HB, 2017 to be 28.7% in Ethiopia[33], 24.5% in Cameroon byNoubiap et al, 2014 [34], 16.4% in Somalia by Hussein et al[35], 12.9% in Ethiopia by Abebaw et al[36] …”
mentioning
confidence: 99%
“…Chronically infected persons are the main reservoirs of HBV which is harbored in their blood and other body fluids like saliva, semen, vaginal secretions and tears with concentrations of HBV deoxyribonucleic acid being high in blood or serous exudates compared to mucosal secretions. Transmission is mainly through sexual intercourse, parenteral contact or mother to child during birth, depending on epidemiological patterns within geographical areas [ 3 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization (WHO) estimates that 2 billion people worldwide have serological evidence of HBV infection, and that this illness causes 1 million deaths annually. Approximately 257 million people are chronically infected with majority residing in low and middle-income countries, particularly in Africa [1][2][3][4]. In Kenya, studies have reported Hepatitis B surface antigen prevalence rate ranging from 5% to 30% in the general population [5].…”
Section: Introductionmentioning
confidence: 99%